HARMONIOUS INTERACTION AMONG ETHNICAL COMMUNITIES IN REGIONAL DEVELOPMENT - Sismudjito Sismudjito; Badaruddin Badaruddin; Suwardi Lubis (Indonesian Journal of Geography, 2013)
This research was conducted in 13 villages of Secanggang district, North Sumatra Province-Indonesia. This study describes the capacity and condition of harmonious interaction among ethnical communities in regional development, which focuses on villager motivation as intervening variables. Motivation is a very important instrument in bridging the concepts of harmony among communities towards regional development. Development of a region is implemented through harmonious interaction among various ethnic communities that can serve motivation as an intervening variable. This study uses a combination of qualitative (exploratory) and quantitative method.  There is one factor that plays a role as a determinant factor in causing successful development. The interaction, either directly or indirectly, generates assimilation between ethnical cultures.